Modeling the Influence of CYP2C9 and ABCB1 Gene Polymorphisms on the Pharmacokinetics and Pharmacodynamics of Losartan - Dmitry Babaev; Elena Kutumova; Fedor Kolpakov (Pharmaceutics)
Background/Objectives: Hypertension is a pathological condition characterized by elevated systolic and/or diastolic blood pressure. A range of pharmacotherapeutic agents are available to treat this condition and prevent complications, including the angiotensin II AT1-receptor blocker losartan. Following oral administration, losartan is exposed to a variety of enzymes that facilitate its metabolism or transportation. The structural characteristics of the genes that encode the enzymes may potentially impact the pharmacokinetics and pharmacodynamics of losartan, thereby modulating its effects on the treatment process. Methods: In this study, a computational model of losartan pharmacokinetics was developed, taking into account the influence of different alleles of the CYP2C9 gene, which plays a pivotal role in losartan metabolism, and the ABCB1 gene, which is responsible for losartan transport. Results: Alterations in the modeled activities of the enzymes encoded by CYP2C9 and ABCB1 result in changes in the losartan and its metabolite profiles that are consistent with known experimental data in real patients with different CYP2C9 and ABCB1 genotypes. Conclusions: The findings of the modeling can potentially be used to personalize drug therapy for arterial hypertension.